Gaya Kepemimpinan Kepala Madrasah dalam Meningkatkan Kompetensi Profesional Guru Madrasah Tsanawiyah As’adiyah No. 3 Atapange Wajo Sulawesi Selatan - Ahmad Muktamar B; Ariswanto Ariswanto; Nurnaningsih A (Departement of Mathematics Education, 2020)
The head of the madrasa as the highest leader in the education unit, has a very vital role in the management of the madrasa, because the progress of the institution is under his responsibility. The creativity of the madrasa head becomes a necessity so that he is able to manage the madrasa organization properly and correctly. The implication is that the success is in the form of teacher output and professionalism. The purpose of this study was to analyze the leadership of the madrasah head in improving the professional competence of teachers with the research subject of Madrasah Tsanawiyah As'adiyah No.3 Atapange. This research is a case study research, with a qualitative approach. Sampling used a purposive sampling technique, namely the leadership of the madrasa head in improving the professional competence of teachers. Data collection through questionnaires, interviews, and observation. The collected data is then organized, interpreted and analyzed repeatedly, in order to develop concepts and abstract field findings. The results showed that madrasah heads have a democratic leadership style in improving teacher professional competence, while the strategy used is collaborative, namely paying attention to personal behavior and the condition of teachers, listening to ideas and suggestions from teachers, resolving and clarifying mistakes, providing input and trying to solve teacher problems, dividing tasks together, setting an example, acting according to the ability of the teacher.